COMPARISON OF ANGLE OPENING DISTANCE AND TRABECULAR IRIS SPACE AREA BEFORE AND AFTER LASER PERIPHERAL IRIDOTOMY IN ANGLE CLOSURE DISEASE: Abstract Only - Ramdhani, Rizki Fasa; Rifada, R. Maula; Irfani, Irawati; Gustianty, Elsa; Umbara, Sonie (Majalah Oftalmologi Indonesia, 2023)
Introduction and Objective: Laser peripheral iridotomy (LPI) is the standard first-line therapy in angle closure disease to increase anterior chamber angle width. Spectral Domain Anterior Segment Optical Coherence Tomography (SD AS-OCT) is an instrument that has a quantitative parameter to measure anterior chamber angle. Angle opening distance (AOD) and trabecular iris space area (TISA) are quantitative parameters in SD AS-OCT. The purpose of this study is to compare AOD and TISA before and one week after LPI in angle closure disease. Methods: This is an analytical prospective study with a cross-sectional study design. Twenty-two eyes with angle closure disease that met inclusion and exclusion criteria underwent LPI and SD AS-OCT before and one week after LPI. Analysis was performed using SD AS-OCT parameters, such as AOD (AOD500, AOD750) and TISA (TISA500, TISA750) in the temporal, nasal quadrants, and average. Results: Twenty-two eyes with angle closure are divided into nine eyes with primary angle closure suspect, seven eyes with primary angle closure, and six eyes with primary angle closure glaucoma. The mean age of participants was 57.86±7.63 years. There was a significant increase in AOD500, AOD750, TISA500, and TISA750 in the temporal and nasal quadrants, as well as in the average (P=0.0001) based on a paired t test or Wilcoxon as an alternative. Average AOD750 had the highest T-value (T= 6.329) with a mean 0.20±0.096 before LPI and 0.31±0.144 one week after LPI. Conclusion: There was a significant increase in AOD and TISA after one week LPI in angle closure disease.